2012
DOI: 10.1124/mol.112.078485
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Decreases Specificity Protein 1 (Sp1) Level via Increasing the Sumoylation of Sp1 to Inhibit Lung Cancer Growth

Abstract: Previous studies have shown that the inhibitory effect of betulinic acid (BA) on specificity protein 1 (Sp1) expression is involved in the prevention of cancer progression, but the mechanism of this effect remains to be delineated. In this study, we determined that BA treatment in HeLa cells increased the sumoylation of Sp1 by inhibiting sentrin-specific protease 1 expression. The subsequent recruitment of E3 ubiquitin-protein ligase RING finger protein 4 resulted in ubiquitin-mediated degradation in a 26S-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 44 publications
5
47
0
Order By: Relevance
“…Our recent studies showed that Sp1 increased the growth of lung cancer cells, but inhibits metastatic activity [23, 32]. In the present study, we found that Sp1, which accumulated in the early stages of cancer, positively regulated miR-182 gene expression to silence FOXO3 expression and thereby promote cancer cell growth.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Our recent studies showed that Sp1 increased the growth of lung cancer cells, but inhibits metastatic activity [23, 32]. In the present study, we found that Sp1, which accumulated in the early stages of cancer, positively regulated miR-182 gene expression to silence FOXO3 expression and thereby promote cancer cell growth.…”
Section: Discussionsupporting
confidence: 65%
“…Our previous studies demonstrated that Sp1 is involved in Kras G12D -induced lung tumorigenesis [23, 32]. Using cDNA microarray analysis, we found that Sp1 increased oncogene expression and decreased tumor suppressor gene expression.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…An increasing number of studies suggest that SP1 regulates a variety of biological functions, including cell survival, proliferation, differentiation, migration and invasion (32)(33)(34). Additionally, several compounds with anti-tumor effects, which target SP1 have been developed or are in development, and some of them are currently used clinically for cancer treatment (35)(36)(37)(38). Therefore, SP1 has been suggested to be a novel target for cancer therapy due to the cancer-associated functions of the protein.…”
Section: Discussionmentioning
confidence: 99%